2008
DOI: 10.1107/s1744309108037056
|View full text |Cite
|
Sign up to set email alerts
|

Purification, crystallization and X-ray structures of the two manganese superoxide dismutases fromCaenorhabditis elegans

Abstract: PDB References: manganese superoxide dismutase 3dc6, r3dc6sf; 3dc5, r3dc5sf. Caenorhabditis elegans expresses two manganese superoxide dismutase enzymes (MnSOD-2 and MnSOD-3) that are targeted to the mitochondrion. MnSOD-2 is constitutively expressed, while synthesis of MnSOD-3 is inducible. The structures of these two mononuclear metalloenzymes have been determined to 1.8 and 1.7 Å resolution, respectively. Pink crystals formed in space group P4 1 2 1 2 for each, with unit-cell parameters a = b = 81.0, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…We generated a Drosophila SOD2 homology model using the program MUSTER (Wu and Zhang ) and the structure of the C. elegans manganese superoxide dismutase (3DC6) (Trinh et al. ) as the structural template (64% identical: Fig. a).…”
Section: Resultsmentioning
confidence: 99%
“…We generated a Drosophila SOD2 homology model using the program MUSTER (Wu and Zhang ) and the structure of the C. elegans manganese superoxide dismutase (3DC6) (Trinh et al. ) as the structural template (64% identical: Fig. a).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, the crystal structure studies revealed that human MnSOD is a homotetramer whicheach monomer consists of 198 amino acids and is divided into N-terminal helices and a mixed C-terminal a/b domain (Borgstahl et al 1992;Wagner et al 1993). Moreover, many site-specific mutagenesis studies indicated that several residues in C-terminal domain associate with the interactions at the active site as well as the interactions at dimer interface that shown to be important for SOD activity (Borgstahl et al 1992;Sheng et al 2013;Trinh et al 2008;Wagner et al 1993). Therefore, decrease of enzymatic activity in our case could be probably due to the disturbance of the C-terminal fused peptides at active site or dimer interface.…”
Section: Discussionmentioning
confidence: 97%
“…The crystal structures of Mn-SOD from Caenorhabditis elegans [50], and E. coli [49] suggest that the dimer interface is located near the active site of each monomer and contributes to the integrity of the active site of the enzyme. In human SOD tetrameric complex that is formed by dimerization of two dimeric subunits, the dimer interface between the subunits also play important role in thermostability and activity [18,51].…”
Section: Discussionmentioning
confidence: 98%